If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2) + -1(-1b) = 6 2 + -1(-1b) = 6 Remove parenthesis around (-1b) 2 + -1 * -1b = 6 Multiply -1 * -1 2 + 1b = 6 Solving 2 + 1b = 6 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1b = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 1b = 6 + -2 1b = 6 + -2 Combine like terms: 6 + -2 = 4 1b = 4 Divide each side by '1'. b = 4 Simplifying b = 4
| 118=-8+7(8-2x) | | (-8)+x=-3 | | 2w^2+3w=324 | | P(p-3)-6p-18=0 | | 7y(3x+2y)= | | 8/14x=6/10 | | 8/14=6/10 | | 28y-187=15x | | 5/9x=60 | | 7p^2-12p-2=5p-8 | | -2x+8=3x+10 | | 63=6n+3n-2n | | 15y+187=28x | | 6h^2+26h-2=-10 | | 0.36*(11/2) | | x^5+540=0 | | 2.5x+2.8=-1.2x+9.8 | | F(x)=8-2x-x^2 | | (x+6)=2(1-x) | | 2.3x+2.8=-1.3x+9.8 | | 4m+5m-9=3m+m+6 | | 6k^2+k-12=0 | | 4x-3/5x÷4x^2-5/5 | | x^5-x^4-x^3+x^2-2x+2=0 | | 2.5x=11+3x | | X^2-9x-56=0 | | r/2-r/3=3 | | cot^2(x)=3 | | 25/4=R/5 | | 4y^2=400 | | .1*.56*x+.5x=48000 | | 2(4m-2)-4=-64 |